Firearm Deaths in America: Can We Learn From 462, 000 Lives Lost?. Issue 3 (September 2017) - Resnick, Shelby; Smith, Randi N.; Beard, Jessica H.; Holena, Daniel; Reilly, Patrick M.; Schwab, C. William; Seamon, Mark J.
Abstract : Objective: We sought to determine whether state firearm legislation correlated with firearm-related fatality rates (FFR) during a 15-year period. Background: The politicized and controversial topic of firearm legislation has been grossly understudied when the relative impact of American firearm violence is considered. Scientific evidence regarding gun legislation effectiveness remains scant. Methods: Demographic and intent data (1999–2013) were collected from the Centers for Disease Control and Prevention's Web-Based Injury Statistics Query and Reporting System database and compared by state firearm legislation rankings with respect to FFR. State scorecards were obtained from firearm-restrictive (Brady Campaign/Law Center against Gun Violence [BC/LC]) and less-restrictive (National Rifle Association) groups. FFR were compared between restrictive and least-restrictive states during 3 periods (1999–2003, 2004–2008, 2009–2013). Results: During 1999 to 2013, 462, 043 Americans were killed by firearms. Overall FFR did not change during the 3 periods (10.89 ± 3.99/100, 000; 10.71 ± 3.93/100, 000; 11.14 ± 3.91/100, 000; P = 0.87). Within each period, least-restrictive states had greater unintentional, pediatric, and adult suicide, White and overall FFR than restrictive states (all P < 0.05). Conversely, no correlation was seen, during any of the 3 time periods, with either homicide or Black FFR—population subsets accounting for 41.7% of firearm deaths. Conclusions: Restrictive firearm legislation is associated with decreased pediatric, unintentional, suicide, and overall FFR, but homicide and Black FFR appear unaffected. Future funding and research should be directed at both identifying the most effective aspects of firearm legislation and creating legislation that equally protects every segment of the American population.